Development of artificial intelligence algorithm for the analysis and prediction of car accidents on the roads of Peru - Meneses Claudio, Brian Andreé (2023)
In recent years in Peru, there has been an increase in car accidents that have occurred on the roads. Where these figures are worrying because year after year, the curve of accidents and deaths skyrockets without having sought a definitive solution; only in these last 5 years the accident curve has increased to a thousand accidents per year where a definitive solution has not been seen, causing these accidents to cause fear in the Peruvian and foreign populations who want to get to know this beautiful country and its cultural diversity. Therefore, in this research, it has been proposed to develop an artificial intelligence algorithm to be able to analyze and predict car accidents throughout Peru, with the final result that these final results can serve as strategies for the development of emerging technologies to be able to counteract these accidents. Automobile, the final data of this investigation is to be able to specify where these accidents are occurring most through a set of collected and cleaned data to be able to provide much more precise analysis and apply a decision tree model to be able to identify where there is a probability that they occur these accidents again. This research is intended to contribute to the scientific community.